Consequences of the implementation of Fund of Maintenance and Development of Fundamental School and Teaching Valorization (FUNDEF) in the basic education in the municipalities of Limeira and Santa Gertrudes - SP - Maria Helena Schuveter; Theresa Maria de Freitas Adrião (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The objective of the article is to analyze the consequences that implement of Fund of Maintenance and Development of the Fundamental School and Teaching Valorization (FUNDEF) in the basic education in the municipals of Limeira and Santa Gertrudes concerning the dynamic of responsibility between state and municipalities and to the composition of the educational expenses during the period 1996-2002. To this it a accomplished both survey and bibliographic analysis connected on the subject and documental research next to the administration municipal organs in order to collect and the analyze of empirical datum This paper presents in a result of the state research named in Implementation Accompaniment of Fundef in the state of São Paulo, and bonding national to a research about Fundef implementation in eleven Brazilian states.